Preferences and beliefs in ingroup favoritism. - Everett, J; Faber, N; Crockett, M (Frontiers, 2015)
Ingroup favoritism—the tendency to favor members of one’s own group over those in other groups—is well documented, but the mechanisms driving this behavior are not well understood. In particular, it is unclear to what extent ingroup favoritism is driven by preferences concerning the welfare of ingroup over outgroup members, vs. beliefs about the behavior of ingroup and outgroup members. In this review we analyze research on ingroup favoritism in economic games, identifying key gaps in the literature and providing suggestions on how future work can incorporate these insights to shed further light on when, why, and how ingroup favoritism occurs. In doing so, we demonstrate how social psychological theory and research can be integrated with findings from behavioral economics, providing new theoretical and methodological directions for future research.